Dual-specificity tyrosine phosphorylation-regulated kinase 1A (DYRK1A) inhibitors: a survey of recent patent literature. (2nd November 2017) - Nguyen, Thu Lan; Fruit, Corinne; Hérault, Yann; Meijer, Laurent; Besson, Thierry
ABSTRACT: Introduction : Dual-specificity tyrosine phosphorylation-regulated kinase 1A (DYRK1A) is a eukaryotic serine-threonine protein kinase belonging to the CMGC group. DYRK1A hyperactivity appears to contribute to the development of a number of human malignancies and to cognitive deficits observed in Down syndrome and Alzheimer's disease. As a result, the DYRK1A kinase represents an attractive target for the synthesis and optimization of pharmacological inhibitors of potential therapeutic interest. Like most tyrosine kinase inhibitors developed up to the market, DYRK1A inhibitors are essentially acting by competing with ATP for binding at the catalytic site of the kinase. Areas covered : This paper reviews patent activity associated with the discovery of synthetic novel heterocyclic molecules inhibiting the catalytic activity of DYRK1A. Expert opinion : Despite the important role of DYRK1A in biological processes and the growing interest in the design of new therapeutic drugs, there are only few patented synthetic DYRK1A inhibitors and most of them were and are still developed by academic research groups, sometimes with industrial partners.